Body Composition and Serum Total Calcium Were Associated With Blood Pressure Among Children and Adolescents Aged 7–18 in China: A Cross-Sectional Study - He, Huijing; Pan, Li; Du, Jianwei; Liu, Feng; Jin, Yuming; Ma, Jingang; Wang, Li; Jia, Pengben; Hu, Zhiping; Shan, Guangliang (Frontiers in Pediatrics, 2019)
Background: This study aimed to assess the prevalence of childhood pre-hypertension and hypertension (elevated blood pressure, EBP) and explore their risk factors, especially the role of body composition and serum total calcium on EBP. Methods: From Nov 2013 to Jul 2014, a cross-sectional study was conducted in Hainan and Shaanxi Provinces in China. 2283 children and adolescents aged 7-18 underwent anthropometric and blood pressure measurements. Fasting blood was collected and serum total calcium was tested. Blood pressure standards from the updated Fourth Report on the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents were used to classify BP groups based on age, sex and stature. Results: The overall prevalence of pre-hypertension and hypertension were 8.36% and 7.06%, respectively. Boys, older age, living in Hainan Province, excess adiposity and higher level of serum total calcium were found to be associated with EBP. Lean subjects had an average 3.87 mmHg decrease in systolic blood pressure (SBP) than normal weight groups. In contrary, overweight/obesity had increased SBP (3.69 mmHg) and diastolic blood pressure (DBP) (2.58 mmHg) than the normal weight group. Participants with high-level serum total calcium had a 1.60 mmHg increased SBP and 1.77 mmHg increased DBP than the low-level group. Compared with normal weight individuals, lean subjects appeared to have decreased odds of EBP (OR=0.65, 95% CI: 0.43-0.98) but overweight/obese individuals were more likely to have EBP (OR=2.67, 95% CI: 1.68-4.25). High-level of serum total calcium was associated with increased odds of EBP, the OR (95% CI) was 1.51 (1.17 to 1.94). The restrict cubic spline presented a linear relationship between serum total calcium and OR of EBP (P < 0.001). Conclusions: Body composition and serum total calcium were positively associated with blood pressure in children and adolescents. Serum calcium could be considered as an untraditional risk factors for high blood pressure screening along with other body composition indexes in clinical settings.